Awareness and knowledge of diagnostic reference levels in computed tomography among radiographers in public and private hospitals in Selangor / Norasyikin Ishak [et al.] - Ishak, Norasyikin; Zakaria, Faikah; Ali, Mohd Hanafi; Che Zakaria, Wan Farah Wahida (Faculty of Health Sciences, Universiti Teknologi MARA, 2022)
Diagnostic Reference Level (DRL) is an efficient tool for optimising patient protection in medical exposures during diagnostic and interventional procedures without jeopardising the diagnostic information in the image. DRLs have limited value without awareness and knowledge. The purpose of this study was to determine awareness and knowledge of DRL in CT among radiographers in public and private hospitals in Selangor. An online questionnaire survey was administered to radiographers (n=98) in the selected seven public and seven private hospitals in Selangor via social media platforms. The study demonstrated that radiographers working in the private hospitals (61.2%) had high level of awareness than those working in public hospitals (32.7%). Additionally, it was discovered that public hospital radiographers (63.3%) had a higher degree of knowledge than private hospital radiographers (36.7%). Although most of the radiographers have a good level of awareness and knowledge of DRL in CT, enhanced training and re-training should be performed to improve the current practice and update the radiographer's knowledge of the current issues and topics on dose optimization in CT. This two-tier health care system should work as a team when involving with patients' safety to provide a good service to the community.